Structural and electrical properties of hexanoyl chitosan-based polymer electrolyte / Fadiatul Hasinah Muhammad - Muhammad, Fadiatul Hasinah (2010)
The insolubility of chitosan in a wide range of organic solvents has limited its practical application especially in electrochemical systems. In order to improve its solubility, acyl modification of chitosan was carried out in the present study. Films of hexanoyl chitosan-based polymer electrolyte were prepared by solution casting technique. Lithium perchlorate (LiC104) was used as the doping salt while titanium oxide (Ti02) was used as the inorganic filler. In the present study, the plasticized hexanoyl chitosan-based polymer electrolyte was prepared by employing dimethyl carbonate (DMC) as the plasticizing solvent. The X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR) and impedance spectroscopy (IS) were used to characterize the prepared samples. With addition of 30 wt.% LiC104, the conductivity of hexanoyl chitosan-based polymer electrolyte was enhanced from 2.37 x 10' 13 to 1.85 x 10"5 S cm'1. For composite polymer electrolyte system, the highest ionic conductivity was achieved at 3.06 x 10~4 S cm"1 with incorporation of 6 wt.% TiC>2. The highest ionic conductivity value of 4.09 x 10"4 S cm' 1 was obtained with addition of 15 wt.% DMC to hexanoyl chitosan-LiCKVTiC^ electrolyte system. The conductivity increased is due to the increase in the number of free ions and their mobility while the decrease in conductivity is attributed to the ion association which decreases the number of charge carriers available for ionic conduction. Conductivity of hexanoyl chitosan-based polymer electrolytes was also studied as a function of temperature ranging from 283 to 333 K. the conductivity is found to increase with increasing temperature. The regression values, R2 are in the range of 0.97 to 0.99 indicating that all points stretch out in an almost straight line and therefore implying that the conductivity is thermally assisted and can be described by Arrhenius law. Ac conductivity and scaling behaviour of hexanoyl chitosan-based polymer electrolytes were studied at different temperatures. The Jonsher’s universal power law was used to discuss the ac conductivity behaviour of the samples. The temperature dependence of the power law exponent s for the salted hexanoyl chitosan follows the Overlapping Large Polaron Tunneling (OLPT) model while the conduction mechanism for composited hexanoyl chitosan-based polymer electrolyte systems are interpreted based on the Correlated Barrier Hopping (CBH) model.